Praktik Jual Beli Minyak Solar Eceran Dalam Perspektif Ibnu Taimiyah - Elman Johari; Orin Oktasari; Resi Julita (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: The purpose of this article is to find out the process of buying and selling retail diesel fuel in PondokKelapa Village, Central Bengkulu Regency, as well as IbnuTaimiyah’s views on the process of buying and selling retail diesel fuel in PondokKelapa Village, Central Bengkulu Regency. District, and how to do it from his perspective. In this article, this type of research uses field research, namely research whose purpose is to study symptoms or events that occur in community groups. Descriptive qualitative research with preference analysis is used in this study. Measurement fraud occurs during retail diesel sales and purchases. When determining how much solar to retail, some dealers err. The merchant has harmed the buyer through this scam; in Islam, it is against the law to deceive buyers and sellers. The conclusions of this article include that some traders engage in fraudulent trading, particularly by lowering the dosage. even though Ibn Taimiyah strictly forbade fraud, especially in Islam. From the point of view of Ibn Taimiyah, buying and selling fraud, especially reducing the dose, is an illegal act because it can harm one of the parties. According to Ibn Taimiyah, it is against the law to lie, diminish, or cheat in business or trade. In the case of sellers buying and selling diesel, it is expected that they are in accordance with the location being studied, in particular and the general public, to eliminate fraud. Keywords: Sell, Buy & Solar